2021
DOI: 10.7759/cureus.17519
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rheumatoid Arthritis on Bone Loss: Links to Osteoporosis and Osteopenia

Abstract: Rheumatoid arthritis (RA) is an autoimmune chronic connective tissue disease that produces persistent systemic inflammation, with joint inflammation leading to function loss and joint destruction. Low bone mass causes skeletal bone loss, commonly referred to as osteopenia or osteoporosis.We conducted this literature review to examine the relationship between RA and osteoporosis and the variables contributing to this connection. We used articles from the US National Library of Medicine (PubMed), Google Scholar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It has been demonstrated that many risk factors contribute to this association, such as glucocorticoid use, estrogen hormone effects, chronic joints inflammation, and genetics. 59 Furthermore, OP is one of the most severe comorbidities of RA. 60 The KEGG results in this study also illustrated that the RA signaling pathway is the core pharmacological mechanism of RLA against OP and four OP-related genes were regulated by RLA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that many risk factors contribute to this association, such as glucocorticoid use, estrogen hormone effects, chronic joints inflammation, and genetics. 59 Furthermore, OP is one of the most severe comorbidities of RA. 60 The KEGG results in this study also illustrated that the RA signaling pathway is the core pharmacological mechanism of RLA against OP and four OP-related genes were regulated by RLA.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that many risk factors contribute to this association, such as glucocorticoid use, estrogen hormone effects, chronic joints inflammation, and genetics. 59 Furthermore, OP is one of the most severe comorbidities of RA. 60 The KEGG results in this study…”
Section: Food and Function Papermentioning
confidence: 99%
“…Rheumatoid arthritis: rheumatoid arthritis is an autoimmune disorder that can lead to joint damage and bone loss, increasing the risk of osteoporosis (18).…”
Section: Implication For Health Policy/practice/research/ Medical Edu...mentioning
confidence: 99%
“…RA is an autoimmune disorder that attacks the body's defense system and primarily causes inflammation in the joints of the knee or fingers. In addition, RA affects other organs, including the eyes, lungs, and heart, and RA-induced chronic inflammation can impact bone absorption and osteolysis [2]. Currently, no available drug can completely cure RA.…”
Section: Introductionmentioning
confidence: 99%
“…RA-induced symptoms include joint swelling, pain, and joint stiffness [2]. Since the most typical symptoms of RA are inflammation and pain, the studies for developing treatment drugs have focused mainly on reducing inflammation status [3,5].…”
Section: Introductionmentioning
confidence: 99%